Picture the 20s exhibit - Unidentified photographer (Colorado State University. Libraries, 1986)
Photograph of "Picture the Twenties" exhibit installation held at the Gustafson Gallery in Fall 1986. In the foreground, there is a movie projector with theater seating. In the background, there are several dresses on display.
Keywords: Fashion -- History; Fashion -- Exhibitions